Chronic Kidney Disease in Patients with Hip Fracture: Prevalence and Outcomes - Alexander Fisher; Jo-Wai Douglas Wang; Paul N. Smith (International Journal of Clinical Practice)
Objective. Although the association between chronic kidney disease (CKD) and osteoporotic fractures is well established, data on CKD combined with hip fracture (HF) are scarce and controversial. We aimed to assess in patients with HF the prevalence of CKD, its impact on hospital mortality and length of stay (LOS) and to determine the prognostic value of CKD to predict hospital outcomes. Methods. Prospectively collected clinical data were analysed in 3623 consecutive HF patients aged ≥65 years (mean age 83.4 ± 7.50 [standard deviation] years; 74.4% females). Results. CKD among older patients with HF is highly prevalent (39.9%), has different clinical characteristics, a 2.5-fold higher mortality rate, and 40% greater risk of prolonged LOS. The strongest risk for a poor outcome was advanced age (>80 years). The risk of death substantially increases in combination with chronic disorders, especially coronary artery disease, anaemia, hyperparathyroidism, and atrial fibrillation; models based only on three variables—CKD stage, age >80, and presence of a specific chronic condition—predicted in-hospital death with good discrimination capability (AUC ≥ 0.700) and reasonable accuracy, the number needed to predict ranged between 5.7 and 14.5. Only 12% of HF patients received osteoporotic drugs prefracture. Conclusion. In HF patients with CKD, the risk of adverse outcomes largely increases in parallel with worsening kidney function and, especially, in combination with comorbidities; models based on three admission variables predict a fatal outcome. Assessment of renal function is essential to preventing osteoporotic fractures.